2020
DOI: 10.1159/000510875
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Atypia Is a Necessary Factor for Diagnosis of Primary Ovarian Fibrosarcoma: A Case Report and Literature Review

Abstract: • Primary ovarian fibrosarcoma is a rare malignant tumor with few case reports. • The latest WHO histological classification of ovarian tumors emphasizes active mitotic figures, but mild nuclear atypia does not signify the diagnosis of fibrosarcoma. • In many cases, diagnosis is still based on differences in mitotic figures but ignores the degree of nuclear atypia. Novel Insights • Nuclear atypia is a necessary factor for diagnosis of ovarian fibrosarcoma. • FIGO stage, treatment methods, and tumor size may no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Because there have been no reports of solid ExG-OvTs larger than the present case [ 2 6 ], it was initially difficult to understand the patient's pathological condition and determine the proper surgical treatment. Therefore, we conducted a literature search, using the MEDLINE database, of ExG-OvTs to investigate the clinicopathological characteristics and postoperative complications associated with these tumors.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Because there have been no reports of solid ExG-OvTs larger than the present case [ 2 6 ], it was initially difficult to understand the patient's pathological condition and determine the proper surgical treatment. Therefore, we conducted a literature search, using the MEDLINE database, of ExG-OvTs to investigate the clinicopathological characteristics and postoperative complications associated with these tumors.…”
Section: Discussionmentioning
confidence: 96%
“…However, since extremely giant ovarian tumors (ExG-OvTs) are rare, most of relevant reports are just case reports and there are few reports that investigated a certain number of ExG-OvTs [ 1 ]. As for solid ExG-OvTs, there have been only a few case reports [ 2 6 ]. ExG-OvT patients experience many symptoms, including a marked decrease in activities of daily living, malnutrition, dehydration, and dyspnea [ 2 , 7 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since FS is a malignant tumor, does a giant tumor predict a poor prognosis? According to the researches of Zhang et al and Sulkowski et al, tumor size had no differential influence on the survival prognosis of FS patients with ovarian and infantile, respectively [ 18 , 19 ]. However, Ma et al found that a tumor size more than 5 cm and a Ki-67 index over 30% were associated with poor OS in patients with primary intracranial FS [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moderate to marked atypia along with high mitotic activity (>4 mitoses per 10 HPFs), are criteria to differentiate them from cellular and mitotically active fibromas [19,26]. Nuclear atypia has been found to be the only criteria associated with poor patient prognosis [55]. Thus, in the case of a high mitotic count but absence of atypia, the classification as cellular and mitotically active fibroma is recommended [8].…”
Section: Fibrosarcomamentioning
confidence: 99%
“…The immunoprofile of ovarian fibrosarcoma is not specific [10]. Fibrosarcomas may exhibit focal staining with sex cord-stromal immunomarkers, especially inhibin, and are typically negative for CD10 [8,55,56] and positive for vimentin and smooth-muscle actin [10,52]. The expression of progesterone and estrogen receptors is variable [10], complicating the differential diagnosis with fibrosarcoma from soft tissues.…”
Section: Fibrosarcomamentioning
confidence: 99%